Analisis Dampak Sosial Ekonomi Kegiatan Arisan Sembako Hajatan Di Desa Harapan Makmur Kecamatan Rantau Rasau Kabupaten Tanjung Jabung Timur (Studi Akad Arisan Sembako Dilihat Dari Ekonomi Syariah) - Ratna Yulistiani; Tarmizi; Ahmad Syahrizal (CV. KAMPUS AKADEMIK PUBLISING, 2023)
This study aims to find out about: Analysis of the Socio-Economic Impact of the Sembako Social Gathering Activities in Harapan Makmur Village, Rantau Rasau District, Tanjung Jabung Timur Regency (Study of the Basic Food Arisan Contract seen from Sharia Economics). The research method in this paper is descriptive qualitative, with data collection techniques in this study using observation, interviews and documentation techniques. Based on the research that has been done, it can be concluded that the results are as follows: The practice of social gathering activities that took place in Harapan prosperous village, Rantau Sasau sub-district, Tanjung jabung district, Jambi Timur, was carried out with the aim of helping. Then the implementation is carried out in an indefinite period of time and there is no lottery system carried out in it because the determination of who will receive the arisan is adjusted to the needs of its members only. This basic food gathering activity has a positive impact on the social and economic aspects of the Harpan Makmur village community which is economically safe with this social gathering activity, the community is lightened in terms of the burden of the celebration costs and socially this arisan activity can also strengthen community relations, especially arisan members. Sharia Economic Review of the Basic Food Arisan Implementation Contract, the practice of organizing social gatherings has met the legal principles of Islamic muamalah, then what is in accordance with the basic food gathering practice for the celebration is a qardh contract.